Permanence des ordres d’enseignement : réseaux, orientation et classes sociales. L’exemple de la formation agricole - Laure Minassian (Recherches en Éducation)
One of the less visible consequences phenomenon of mass education was to promote the emergence of new pupils in agricultural education. Historically divided in two trainings (primary-professional versus secondary-higher school), these two levels are now formally unified. However, this formal unification hides actual fractures. They can be identified inside of two agricultural training institutions located in Loire-Atlantique. At the same level of education, in sectors traditionally dedicated to the children of farmers, the children of workers and employees are more likely to enroll in the ancient primary-professional when the children of farmers enroll more heavily in the ancient upper-secondary school. These social and academic orientations are justified by the pupils through a system of values ​​and personal tastes. In this perspective, the practices of language of pupils in interviews are interesting. They constitute data useful for objectify some effects of domination and social circulation of pupils in school.